cpDNA supports the identification of the major lineages of American Blechnum (Blechnaceae, Polypodiopsida) established by morphology - Gabriel y Galán, José Maria (2013)
Blechnaceae is an important leptosporangiate family (9–10 genera, about 250 species). It is monophyletic and distributed mainly in tropical America and Australasia. Among the species 80% belong to Blechnum, a genus with a very complex taxonomy and uncertain internal relationships. In terms of American diversity, the results of morphological studies have arrived at 8 informal groups. Molecular works on this genus are scarce, and there is no information for the majority of American species. The main objective of this work was to evaluate whether the groups proposed to organise the diversity of American of Blechnum are consistent with a molecular analysis. We sequenced 2 chloroplastic regions from species representing all of the groups. In our molecular analysis most of the informal groups were maintained as well supported clades. Only 2 species, B. brasiliense and B. spicant, appear to be isolated from their alleged relatives. Combining our molecular results with previous morphological knowledge, we propose the recognition of 4 lineages: 1) B. serrulatum , 2) B. spicant, and 3) core Blechnum, which represents a large clade that can be divided into core Blechnum I (arborescent species, cordatoids, and B. brasiliense) and core Blechnum II (epiphytic species and herbaceous terrestrials, both monomorphic and dimorphic groups).